Migration of foreign specialists into the high-tech sector in Iceland and the role of Human Resource Management - Dominique Elísabet James 1991- (2021)
The high-tech sector in Iceland is facing a shortage of people with the right skills and experience. Organizations need to attract and hire foreign specialists to fill their roles. The study aimed to explore what the main reasons are for foreign specialists to migrate into the high-tech sector in Iceland. Furthermore, it explored what tools Human Resources Management (HRM) in high-tech is using to attract and retain foreign specialists but also what challenges HRM is facing with a cross-cultural workforce in the high-tech industry in Iceland. To look at the main reasons for skilled workers migrating to Iceland, a quantitative questionnaire was used that systematically and objectively gathered information. Furthermore, statistical methods were used to analyze the answer that presents and interpret the data. A multiple case study was conducted to shed light on what tools HRM uses to attract and retain a foreign specialists and what challenges come with a cross-cultural workforce. The main conclusion is that high-skilled workers seem to migrate into the high-tech industry in Iceland for economic reasons, such as better employment opportunities and higher salaries. However, lifestyle and climate reasons are also important reasons for staying in Iceland HRM most used tool to attract foreign specialists is LinkedIn and offering competitive salaries. Onboarding programs are often used in order to retain foreign specialists. Moreover, an emphasis is on workplace culture with strong psychological safety and creativity. One of the main challenges HRM is facing with the cross-cultural workforce is language-related with the focus usually on keeping the work language completely in English. Keywords: Human Resource Management, foreign specialists, high-tech, attract, retain